An Advanced Transcriptional Response to Corticosterone After Single Prolonged Stress in Male Rats - Ding, Jinlan; Chen, Xinzhao; Han, Fang; Meijer, Onno C. (Frontiers in Behavioral Neuroscience, 2021)
Stress-related neuropsychiatric disorders are often accompanied by dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis. In patients suffering from posttraumatic stress disorder (PTSD), increased sensitivity of glucocorticoid negative feedback has regularly been observed. Here, we sought to investigate the overall GR responsiveness in the brains of rats exposed to Single Prolonged Stress (SPS), which was developed to model increased negative feedback and other aspects of PTSD. We injected corticosterone or vehicle in 7 days after SPS, and evaluated plasma corticosterone, as well as gene expression in the dorsal hippocampus and amygdala. We observed a strikingly rapid change in expression of established GR target genes (t=30 minutes) only in the SPS group upon exogenous corticosterone injection. Our results extent the notion of increased GR sensitivity in PTSD to include transcriptional responses in the hippocampus.